Diagnosis of Chikungunya infection: a Narrative Review - Khan, Tarek Mahbub (Sir Salimullah Medical College Journal, 2025)
Chikungunya virus (CHIKV) is an arbovirus infects humans that lead to Chikungunya fever, usually characterized by intense joint pain and arthritis. The first case was identified in 1953 at Tanzania of east Africa. As of December 2024, 119 countries and territories have reported cases of Chikungunya and many cases presumed to be under reporting due to diagnostic limitations. The virus is transmitted by Ades aegypti and Ades albopictus. Bangladesh carries a huge burden of Chikungunya virus since 2007 which is gradually increasing. Many factors influences laboratory identification of Chikungunya virus (CHIKV) includes viral strains, patient immune response, time of sample collection from the onset of infection, test sensitivity and specificity, test compliances. Most reliable test for detection of Chikungunya virus is RT-PCR. Loop-mediated isothermal amplification (LAMP) can also be used in resource limited setting but has less sensitivity. Antibody detection depends on time of collection of sample after onset of infection, patient immune response, type of tests. Anti-Chikungunia IgM antibody becomes positive between 3-8 days of onset of infection. IgM capture ELISA (MAC-ELISA) is more sensitive. A fourfold rising titer of anti-IgG antibody in 3 weeks apart often recommended for diagnosis of recent Chikungunya infection. Serology test are less sensitive to RT-PCR or LAMP. Selecting appropriate tests for laboratory diagnosis of Chikungunya is critical in terms of its timing of test, cost effectively, resource mobilization and reliability, sensitivity. Hence a combine approach of clinical judgment and laboratory evidence is important for diagnosis of Chikungunya. Sir Salimullah Med Coll J 2024; 32: 46-51